Pengalaman Komunikasi Pria Pegiat Gym Pengguna Media Sosial Instagram - Kuswandanu, Taqiyuddin; A, Weni; Ema (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the motives, meanings and communication experiences of male gym activists regarding posts related to gum. This research uses a qualitative research method with a phenomenological approach. Data was obtained through an in-depth interview process as well as field and online observations. The theory used is Alfred Schutz's phenomenological theory and Participatory Media Culture theory. The outcomes of the research indicate that the